2020
DOI: 10.1515/ntrev-2020-0034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nano and micro conductive materials on conductive properties of carbon fiber reinforced concrete

Abstract: AbstractIn this study, the pressure sensitivity and temperature sensitivity of the diphasic electric conduction concrete were investigated by measuring the resistivity using the four-electrode method. The diphasic electric conduction concrete was obtained by mixing nano and micro conductive materials (carbon nanofibers, nano carbon black and steel slag powder) into the carbon fiber reinforced concrete (CFRC). The results indicated that, with the increase of conduction time, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 19 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…Its shear resistance and seismic performance of the reinforced components are better than those of ordinary steel tube concrete. According to the different types of fibers composed of FRP, fiber composite materials mainly used in engineering can be divided into carbon fiber-reinforced polymer (CFRP), glass fiber-reinforced polymer (GFRP), aramid fiber-reinforced polymer (AFRP) [18]. Table 2 shows their various indicators.…”
Section: Nanoscale Carbon Fiber Concretementioning
confidence: 99%
“…Its shear resistance and seismic performance of the reinforced components are better than those of ordinary steel tube concrete. According to the different types of fibers composed of FRP, fiber composite materials mainly used in engineering can be divided into carbon fiber-reinforced polymer (CFRP), glass fiber-reinforced polymer (GFRP), aramid fiber-reinforced polymer (AFRP) [18]. Table 2 shows their various indicators.…”
Section: Nanoscale Carbon Fiber Concretementioning
confidence: 99%
“…Many scholars have studied the intelligent response characteristics of the smart hybrid concrete and found that the intelligent response has a coupling effect [117][118][119][120][121]. It is related to the distribution and contact of the mixed fiber in the concrete and is affected by the type of mixed fibers, and the content and proportion of fibers, ambient temperature, and water content [121][122][123][124][125][126]. Dong et al [13] prepared CB/PP smart concrete.…”
Section: Field Response Mechanismmentioning
confidence: 99%
“…In the literature, it has been reported that CF can inhibit microcrack growth in the study on the compressive strength of CF reinforced concrete [23]. Han et al [24] stated that CF reinforced concrete has excellent compressive strength and high flexural strength compared to conventional concrete. Considering the use of industrial waste materials in concrete production and the studies on conductive concrete, research has been carried out to improve the strength properties of concrete by using recycled ferrochrome instead of aggregate.…”
Section: Introductionmentioning
confidence: 99%